Dynamics of groundwater drought in the Yellow River source area and its surface influences - Huiwu Zhang; Gang Liu; Jing He; Yue Hu (Journal of Hydrology: Regional Studies)
Study region: Yellow River source area in China. Study focus: The primary objective of this study is to investigate the dynamic evolution of groundwater drought events in the source area of the Yellow River over the past two decades. By adopting a three-dimensional perspective, the study aims to characterize and quantify the severity of droughts and analyze their spatiotemporal characteristics. In addition, it explores the seasonal relationships between groundwater drought and key surface factors—elevation, slope, and land use. New hydrological insights for the region: This study systematically identifies persistent groundwater drought events and their consistent spatial centers, setting it apart from previous research that primarily focused on single indices or short-term trends. The most severe drought event occurred between 2017 and 2018. By incorporating surface factors such as elevation, slope, and land use, and examining their seasonal interactions with drought patterns, the study reveals that high-elevation, steep-slope areas, as well as regions dominated by bare land or grassland, are more vulnerable to groundwater drought, particularly during winter. In contrast, wetlands and water bodies exhibit low and stable drought risk. Unlike prior studies that mainly emphasized macro-level drivers, this research places greater focus on surface conditions influencing groundwater drought. These findings enhance understanding of hydrological mechanisms in fragile plateau regions and help identify high drought-risk areas for targeted management.